2013
DOI: 10.1097/wnr.0b013e3283647682
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of threat expressions and eye gaze

Abstract: The current study examined the interaction of fearful, angry, happy, and neutral expressions with left, straight, and right eye gaze directions. Human participants viewed faces consisting of various expression and eye gaze combinations while event-related potential (ERP) data were collected. The results showed that angry expressions modulated the mean amplitude of the P1, whereas fearful and happy expressions modulated the mean amplitude of the N170. No influence of eye gaze on mean amplitudes for the P1 and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Therefore, gaze manipulations may not be salient enough to influence processing at this early sensory stage. This is supported by findings with adults reporting emotion effects during early visual processing but an interaction with gaze only during later processing stages (71).…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, gaze manipulations may not be salient enough to influence processing at this early sensory stage. This is supported by findings with adults reporting emotion effects during early visual processing but an interaction with gaze only during later processing stages (71).…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly in the present study, the differences between direct and averted gaze found in the second negativity of the Lambda complex was not observed in the target locked N170. The majority of previous studies using static images in adult typical populations were unable to find any differences between gaze directions in these components (Grice et al, 2005, Klucharev and Sams, 2004; Nomi, Frances, Nguyen, Bastidas, & Troup, 2013; Taylor, George, & Ducorps, 2001; Taylor, Itier, Allison, & Edmonds, 2001; Yokoyama, Noguchi, & Kita, 2013), with two finding larger N170 for averted gaze (Itier et al, 2007, Watanabe et al, 2002). A similar difference in N170 was observed in Conty et al (2007), where gaze dynamically changed from a neutral position to direct or averted gaze.…”
Section: Discussionmentioning
confidence: 89%
“…It appears then that implicit/explicit processing interacted with emotional expression such that angry expressions influenced early components regardless of tasks, while happy expressions only influenced later components when explicitly attended. This suggests that emotion processing is best explained by emotion specific differences in attention and best fits with a constructivist description of emotion processing [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 87%
“…A recent meta-analysis of a decade’s worth of data addressed two possible accounts for how emotion is processed in the brain: a “locationalist” account, where a specific brain location is responsible for eliciting a particular emotion, and a “psychological constructionist” account, which suggests that processing of emotion is distributed across brain structures [ 4 ]. Recent research investigating the temporal processing of emotion suggests that early processing of emotional stimuli, measured electrophysiologically, were modulated by task [ 5 , 6 , 7 ]. Rellecke et al asked participants to either, explicitly identify the emotional expression of a face stimulus, or implicitly process emotional expression in a passive viewing task.…”
Section: Introductionmentioning
confidence: 99%